1992
DOI: 10.1103/physreva.45.8624
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric studies of liquid crystals under high pressure: Static permittivity and dielectric relaxation in the nematic phase of pentylcyanobiphenyl (5CB)

Abstract: Dielectric studies of a thermotropic-liquid-crystalline substance [pentylcyanobiphenyl (5CB)] under high pressure are reported. Measurements of a complex dielectric permittivity were carried out in the pressure range 0.1 -160 MPa, the frequency range 1 kHz-13 MHz, and the temperature range 287 -343 K. Static permittivities measured at constant pressures are governed by the [2S(T)+1]/T factor. An increase in permittivity with pressure at a constant temperature is interpreted as a result of an increasing molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 17 publications
7
29
0
Order By: Relevance
“…The factor (2 S(p) + 1)T, normalized to the permittivity at high pressure, differed much from that at low pres sures. Especially close to the N-I transition the per mittivity decreased more strongly than according to (4). Because of this effects, together with a systematic decrease with pressure of the activation parameters characterizing the molecular reorientations around the short axes, it was concluded that a relatively low pressure breaks the dipole-dipole correlations in the nematic phase of 5CB.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The factor (2 S(p) + 1)T, normalized to the permittivity at high pressure, differed much from that at low pres sures. Especially close to the N-I transition the per mittivity decreased more strongly than according to (4). Because of this effects, together with a systematic decrease with pressure of the activation parameters characterizing the molecular reorientations around the short axes, it was concluded that a relatively low pressure breaks the dipole-dipole correlations in the nematic phase of 5CB.…”
Section: Discussionmentioning
confidence: 91%
“…dielectric studies of 5CB [4], (1) was used for the analysis of the relationship between the measured permittivities (which were obtained for an unperfectly oriented sample, however) and the or der parameter known form optical measurements [4,13]. Assuming other quantities to be constant and neglecting the induced polarization, the approximate relation eoii -1 oc (2S + 1)/F (4) was discussed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations